Platformisation of Digital Financial Services (DFS): The Journey of DFS in the Global North and Global South - Jain, Pranjal; Blandin, Alex Jordan; O'Neill, Jacki; Perry, Mark; Roach, Matt; Jones, Matt; Ibtasam, Samia; Candello, Heloisa; Chugh, Beni; Shahid, Suleman (CHI 2022, 2022)
The digitization of financial transactions in both Global North and Global South has led to considerable shifts in how money is used, understood, and processed by users, banks, and fintechs. This shift from physical cash to digital media, accelerated by the COVID-19 push for digital transactions, has impacted how users perceive and use digital money and opened avenues for more data collection. This diverse panel proposes a discussion to understand the set of opportunities and challenges around the design of digital financial services (DFS) and data-driven decision-making in DFS. We will create a live working document starting before the panel to document the discussion, which develops during and after the panel. This live document will enable community to engage with a broader audience of researchers and industry, outlining processes, methods, and tools that researchers and practitioners have created to work with users to develop new equitable DFS and further exploration.